Traditional method of fish treatment, microbial count and palatability studies on spoiled fish - Seri Intan Mokhtar; Ambiga Paneer Selvam; Nur Ain Abd Aziz; Seri Bunian Mokhtar (2013)
Aims: To evaluate the microbial count and palatability acceptance of spoiled fish after treatment with traditionally used natural solution. Methodology and results: To compare microbial count of spoiled fish before and after treatment with natural solution practiced by local people in Malaysia, 10 g of spoiled fish was respectively rinsed with 100 mL of 0.1% of natural solution such as Averrhoa bilimbi extract, rice rinsed water, rice vinegar, Citrus aurantifolia extract, salt, flour, and Tamarindus indica extract. Flesh of fish rinsed with rice vinegar was found to be able to reduce microbial count (CFU/mL = 0.37 X 107 ) more than 4.5 times when compared to spoiled fish (CFU/mL=1.67x 107 ). Spoiled fish that was treated with rice vinegar was prepared into a cutlet and fried. The cutlet was subjected to palatability acceptance study by a group of residents in Palm Court Condominium, Brickfields, Kuala Lumpur. The palatability study from the Cronbach alpha shown that the taste have the reliability of 0.802, the aroma has the reliability of 0.888, colour with the reliability of 0.772, texture or mouth feel have reliability of 0.840 and physical structure of the cutlet is 0.829. Conclusion, significance and impact of study: Treatment of spoiled fish using rice vinegar as practice by local people traditionally shown a significant reduction in microbial count and the vinegar-treated fish could be developed into a product that is safe and acceptable by the consumer.